Progressive optic nerve changes in cavitary optic disc anomaly: integration of copy number alteration and cis-expression quantitative trait loci to assess disease etiology - Eileen S. Hwang; Denise J. Morgan; Katie L. Pennington; Leah A. Owen; John H. Fingert; Paul S. Bernstein; Margaret M. DeAngelis (BMC, 2019)
Abstract Background We performed clinical and genetic characterization of a family with cavitary optic disc anomaly (CODA), an autosomal dominant condition that causes vision loss due to adult-onset maculopathy in the majority of cases. CODA is characterized by a variably excavated optic nerve appearance such as morning glory, optic pit, atypical coloboma, and severe optic nerve cupping. Methods Four affected and fourteen unaffected family members of a multi-generation pedigree were phenotyped by visual acuity, intraocular pressure, dilated fundus examination, fundus photography, and optical coherence tomography. Genetic analysis was performed by breakpoint polymerase chain reaction (PCR), long range PCR, and direct Sanger sequencing. The functional relevance of the copy number alteration region was assessed by in silico analysis. Results We found progressive optic nerve cupping in three affected members of a family with CODA. In one individual, an optic pit developed over time from a normal optic nerve. By two independent methods, we detected a previously described intergenic triplication that segregated with disease in all adults of the family. The copy number alteration was also detected in five children with normal optic nerves. eQTL analysis demonstrated that this CNA region regulates expression of up to 4 genes in cis. Conclusions Morning glory, optic pit and atypical coloboma are currently considered congenital anomalies of the optic nerve, but our data indicate that in CODA, the excavated optic nerve appearance may develop after birth and into adulthood. In silico analysis of the CNA, may explain why vairable expressivity is observed in CODA.